Enlist E3™ Soybean Sensitivity and Enlist™ Herbicide-Based Program Control of Sumatran Fleabane (Conyza sumatrensis). (6th June 2018) - Frene, Rafael L.; Simpson, David M.; Buchanan, Marcos Baez; Vega, Ernesto Teran; Ravotti, Maximiliano E.; Valverde, Pablo P.
Abstract: Enlist E3™ soybean, resistant to 2, 4-D, glufosinate, and glyphosate, provides options to control glyphosate-resistant Sumatran fleabane before planting and in crop. Twenty field trials were conducted in Argentina to determine Enlist E3 soybean sensitivity to POST applications of 2, 4-D choline+glyphosate or glufosinate. Maximum injury from a single 2, 4-D choline+glyphosate application at 1X (1140+1140 g ae ha −1 ) and 2X rate was 4% and 13%, respectively, at 3 days after treatment in the temperate Humid Pampa region. Slightly higher injury of 11 and 23% was observed in sub-tropical region of northern Argentina. Injury was transient with recovery occurring within 14 days. Injury caused by sequential applications was equivalent to that caused by single applications. Soybean yield was not affected by single nor sequential applications. In four trials, control programs containing 2, 4-D choline+glyphosate applied PRE and POST provided greater GR Sumatran fleabane control and a 12 to 26% increase in yield compared to 2, 4-D choline+glyphosate applied at PRE only. This research demonstrates the glyphosate-resistant control programs that include 2, 4-D choline, glyphosate, and glufosinate provide excellent GR Sumatran fleabane control.